Analisis Strategi Pemasaran dalam Upaya Meningkatkan Penjualan Industri Keripik Nenas Pasca Pembangunan Jalan Tol Bangkinang-Pekanbaru - Akbar, Rahmad; Yetti, Dzulhijjah; Rahmayani, Merlia; Hasybi, Khairul (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Home Industry Keripik Nenas is a company that produces dry and wet cakes, but they are facing challenges in the form of declining sales. This research aims to identify competitors' advantages using the benchmarking method and to identify the company's strengths, weaknesses, opportunities and threats, as well as designing marketing strategies to increase sales. The results of the benchmarking analysis reveal that competitors have many advantages. Meanwhile, the SWOT calculation results show that Keripik Nenas's main strength is its delicious taste, but this company has a weakness in its limited product variety. Companies have great opportunities in the form of high consumer loyalty to their products, but also face threats from the emergence of similar products on the market. Therefore, from this SWOT analysis, several marketing strategies can be designed to increase sales.